Implementation of Ac-Dc-Ac 3-Level PWM Converter - Tanikonda Kishore Kumar, V Revanth Kumar (Mathematical Statistician and Engineering Applications, 2022)
A three-level pulse width modulation (PWM) technique for ac to dc converter is proposed. Three-phase rectifier based on a double boost configuration with power factor correction is used on the input side. Three-phase three-level voltage source inverter based on a diode clamped scheme is employed in order to reduce the harmonic content of the inverter output voltages. On the rectifier side, the hysteresis current controller is used to track the line current command in phase with the mains voltage. A capacitor voltage compensator is adopted to balance the neutral point voltage in order to maintain good quality voltage waveforms on the output of the inverter. On the inverter side, three-level PWM based on sine-triangular comparison is used to reduce the voltage harmonics.